Psychometric Validation and KR-20 Reliability of a Knowledge Tool for Semi-Intensive Pig Production - Deepjyoti Roy; Chaturvedani, Ajay Kumar; Jayant Goyal; Sanjay Kumar Ravi; Dhananjay Kumar; Anshuman Kumar (Indian Journal of Extension Education, 2025)
An instrument was constructed to assess the pig farmers’ knowledge level regarding scientific pig production under a semi-intensive rearing system. Primary review of relevant literature was the initial step in the identification of relevant items. A list of 42 items was prepared and then refined for preliminary assessment on sixty purposively selected pig farmers hailing from non-sampling areas. Data was collected during 2024-25, through a direct questioning method using an interview schedule by registering dichotomous responses, “correct” and “incorrect”, scored in binary format as “1” and “0”, respectively, for each item. The raw data was analysed to determine item difficulty (P) and item discrimination (D), which sorted thirty relevant items. Validity of selected items was confirmed through a point-biserial correlation test, with all items having an rpb ≥ 0.30. The overall internal reliability of the knowledge tool was established by KR-20 test, which yielded a coefficient value of 0.92, signifying very high reliability of the tool in measuring knowledge of pig farmers. The 30 items, encompassing five well-structured items under six major thematic dimensions, were incorporated to assess the respondents’ knowledge level comprehensively. Based on equal class intervals, the majority of respondents had a medium level of knowledge.